Characteristics of the city and its role in the semantic transformation of Spinning poetry in the Umayyad era - Sabih Dyer Nashmi; Dr. Wasan Sadiq Abbas (Journal of College of Education, 2024)
Urban approaches are reflected through their social, psychological and cultural influences and consequences, and the socio-cultural indicators and pressures that these indicators and cultural pressures entail in terms of syndromes that interact in one way or another with the rhyming buildings, so that the impulses and impulses that are coordinated according to those influences show their characteristics and graphic signs in the nature of the poetic purpose and its linguistic and moral formulations, to form a system of values. Considered, inspired by the geographical environment in which it arose or appeared. Therefore, the nature of research into the organizational structure of urban poetry, whether at the level of form or content, imposes an in-depth study of the general cultural atmosphere that resulted from the various poetic systems, and perhaps the aspect of youth is also of importance in The rest of the places have different atmospheres and environments. Its importance within the urban center is no less than its counterparts, as it is considered a clear and accurate indicator of the narratives of the emotional reality that was compatible with its incubating urban environment. Therefore, this study came to shed light on this important artistic and literary content within human existence in its civilized Arab character. Its most prominent features and transformations are identified within the semantic classification, with its formal and moral aspects
Keywords: the city, significance, Spinning poetry, the Umayyad era